Rational use of NSAIDs and the incidence of potential drug interactions in inpatients with osteoarthritis at the Tangerang City General Hospital - Fauziah, Siva; Aulia, Gina; Nasar, Nur Afni Syariah; Putri, Annisa Septyana; Komarudin, Dede (PT WIM Solusi Prima, 2025)
Background: Osteoarthritis (OA) is a disease that affects articular cartilage, subchondral bone, synovium, capsule, and ligaments. This disease is an overlapping disorder with different etiologies but similar biological, morphological, and clinical outcomes. The rationality of drug use in osteoarthritis must be optimized to achieve optimal therapeutic outcomes. The potential for drug interactions must also be understood to prevent unwanted effects from therapy. Objective: To determine the rationality of drug use and the potential for drug interactions in osteoarthritis patients at Tangerang City General Hospital, focusing on the four principles of appropriate drug use: appropriate patient, appropriate drug, appropriate indication, and appropriate dose. This study is a descriptive observational study with a cross-sectional design and uses retrospective data. Method: The study sample was selected using purposive sampling, considering inclusion and exclusion criteria. The study sample meeting the inclusion criteria consisted of 31 medical records (patients). The data obtained were then compared with the reference standards of the Indonesian Rheumatology Association (IRA). Results: Patient characteristics based on age showed the highest proportion in early elderly (46–55 years) at 41.9%, female gender at 71%, with joint pain location in the feet at 65%, other joints at 23%, and hands at 12.9%. The profile of prescribed osteoarthritis medications was as follows: sodium diclofenac 41.9%, meloxicam 38.7%, ketorolac 12.9%, and mefenamic acid 6.5%. The rationality of patient accuracy, medication, indications, and dosage yielded 100% data related to NSAID use in osteoarthritis patients, with the highest potential for drug interactions occurring in the combination of sodium diclofenac and bisoprolol at 18.2% at a moderate severity level. The mechanism of interaction involves NSAIDs potentially weakening the antihypertensive effects of beta-blockers. The mechanism of NSAID-induced inhibition of renal prostaglandin synthesis results in uninhibited pressor activity, leading to hypertension. Additionally, NSAIDs can cause fluid retention, which also affects blood pressure. Conclusion: The rational use of NSAIDs in terms of the right patient, right drug, right indication, and right dose was 100%, and the total number of PIAO cases found was 11 (28.2%). Of all the cases identified, 8 cases were moderate in severity and 3 cases were minor. The most common drug interactions were between Sodium Diclofenac and Bisoprolol, accounting for 18.2%. Keywords: Drug rationality NSAIDs, Osteoarthritis, Potential drug interactions.